2017
DOI: 10.1161/circulationaha.117.029870
|View full text |Cite
|
Sign up to set email alerts
|

Acute Coronary Syndromes

Abstract: Well into the 21st century, we still triage acute myocardial infarction based on the presence or absence of ST segment elevation, a century-old technology. Meanwhile, we have learned a great deal regarding the pathophysiology and mechanisms of acute coronary syndromes (ACS) at clinical, pathological, cellular, and molecular levels. Contemporary imaging studies have shed new light into the mechanisms of ACS. This review discusses these advances and their implications for clinical management of the ACS for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
151
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(183 citation statements)
references
References 117 publications
1
151
0
1
Order By: Relevance
“…Arterial thrombosis is commonly initiated by vascular endothelial erosions and ruptures of an atherosclerotic plaque 3,4 while venous thrombosis mainly stems from blood stasis. 5 Despite these differences, platelet adhesion/activation, and fibrin deposition as the result of coagulation constitute the fundamental processes of thrombus formation.…”
mentioning
confidence: 99%
“…Arterial thrombosis is commonly initiated by vascular endothelial erosions and ruptures of an atherosclerotic plaque 3,4 while venous thrombosis mainly stems from blood stasis. 5 Despite these differences, platelet adhesion/activation, and fibrin deposition as the result of coagulation constitute the fundamental processes of thrombus formation.…”
mentioning
confidence: 99%
“…Growing attention has been focused on C-reactive protein (CRP), a simply detectable inflammation biomarker, as a possible predictor of AKI and it has been recently recognized that CRP actively contributes in the pathogenesis and progression of AKI, by exacerbating local inflammation, impairing the proliferation of damaged tubular epithelial cells, and promoting the fibrosis of injured renal tissue [11][12][13][14][15]. Moreover, physicians have now become accustomed to use high-sensitivity CRP (hs-CRP), when considering vascular disease risk stratification, as opposed to the use of standard CRP assays that monitor infections and other inflammatory conditions [16][17][18]. In particular, to assess the cardiovascular risk, CRP should be measured by highly sensitive methods that are capable of reliably measuring concentrations within the healthy reference interval [16][17][18].Emerging evidence showed that serum level of CRP acts as a risk factor and, at the same time, as a potential causal factor for both AKI development and severity, which is also seen in AMI patients [15].…”
mentioning
confidence: 99%
“…Moreover, physicians have now become accustomed to use high-sensitivity CRP (hs-CRP), when considering vascular disease risk stratification, as opposed to the use of standard CRP assays that monitor infections and other inflammatory conditions [16][17][18]. In particular, to assess the cardiovascular risk, CRP should be measured by highly sensitive methods that are capable of reliably measuring concentrations within the healthy reference interval [16][17][18].Emerging evidence showed that serum level of CRP acts as a risk factor and, at the same time, as a potential causal factor for both AKI development and severity, which is also seen in AMI patients [15]. In coronary artery disease patients, Gao et al [19], who were the first to perform a retrospective analysis on 4522 patients undergoing elective percutaneous coronary intervention (PCI) with drug-eluting stents, found that elevated pre-procedural CRP was associated with a progressively increased risk of contrast-induced AKI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some plaques are unstable and may “fracture” leading to rapid thrombus formation and severe ischemia of the upstream region [9]. In these cases, physicians may attempt to restore the patency by surgical or endovascular approach.…”
Section: Introductionmentioning
confidence: 99%